2007
DOI: 10.2190/ag.65.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effect on Visual and Spatial Components of Working Memory

Abstract: The aim of this study was to evaluate the effect of aging on the storage of visual and spatial working memory according to Logie's model of working memory (1995). In a first experiment young, elderly, and very old subjects carried out two tasks usually used to measure visual span (Visual Patterns Test) and spatial span (Corsi Block Tapping test). In the second experiment, we modified the encoding time of the Visual Patterns Test so that it was the same as in the Corsi Block Tapping test. Results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
8
25
0
1
Order By: Relevance
“…For the spatial memory task, we found comparable results to other studies using this paradigm and other similar spatial memory paradigms (Greenwood et al, 2005; Beigneux et al, 2007). Computer errors resulted in lost data for four individuals leaving a total of 161 individuals for all analyses with memory performance (see Table 1).…”
Section: Resultssupporting
confidence: 87%
“…For the spatial memory task, we found comparable results to other studies using this paradigm and other similar spatial memory paradigms (Greenwood et al, 2005; Beigneux et al, 2007). Computer errors resulted in lost data for four individuals leaving a total of 161 individuals for all analyses with memory performance (see Table 1).…”
Section: Resultssupporting
confidence: 87%
“…A clear age effect in overall accuracy was observed, with more accurate responding by younger adults, indicating a better ability to store a more precise, finer-grained representation of the target object. This supports previous evidence suggesting that visual short-term memory is age-sensitive (e.g., Beigneux et al, 2007;Brown et al, 2012;Jenkins et al, 2000;Johnson, Logie, & Brockmole, 2010;Logie & Maylor, 2009). In particular, in the context of a visual feature binding task, Peich et al (2013) also investigated fidelity of visual short-term memory representations in older adults using a precision-based measure, and showed that aging was associated with less accurate reproductions of orientation from memory.…”
Section: Model Comparisonssupporting
confidence: 91%
“…A variety of methodologies can be utilized in order to examine age-related differences in visual information processing. For example, one can measure the accuracy in a task after the information has been presented under different encoding time conditions (e.g., Beigneux, Plaie, & Isingrini, 2007;Lecerf & Roulin, 2006;Vaughan & Hartman, 2010), measure the time taken to respond to a visual stimulus (e.g., Deary, Allerhand, & Der, 2009;Gregory, Nettelbeck, Howard, & Wilson, 2008;Hultsch, MacDonald, & Dixon, 2002;Jenkins et al, 2000), or equate the presentation duration needed to reach a set level of performance (e.g., Edwards et al, 2006;Owsley, 2013). These measures have typically indicated slower processing for older adults but there are multiple factors that contribute to these differences.…”
Section: Measuring Processing Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, idosos apresentam dificuldades em realizar duplas ou múltiplas tarefas (Baddeley, 2009b;Glisky & Glisky, 2008). De acordo com os subsistemas da MT, o avanço da idade tem certo efeito sobre a alça fonológica e o esboço visuo-espacial (Beigneux, Plaie, & Isingrini, 2007). Entretanto, segundo Baddeley (1986), o sistema executivo central tende a ser afetado de forma mais significativa, devido a uma falha na eficiência dos sistemas frontais do cérebro durante o envelhecimento.…”
unclassified